Effectiveness and cost-effectiveness of a self-guided internet intervention for social anxiety symptoms in a general population sample: Randomized controlled trial - Powell, J; Williams, V; Atherton, H; Bennett, K; Yang, Y; Davoudianfar, M; Hellsing, A; Martin, A; Mollison, J; Shanyinde, M; Yu, L; Griffiths, K (Journal of Medical Internet Research, 2020)
Background: Many people are accessing digital self-help for mental health problems, often with little evidence of effectiveness. Social anxiety is one of the most common sources of mental distress in the population, and many people with symptoms do not seek help for what represents a significant public health problem.